(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Generally, water considers as the most important components in the development of an area, while groundwater considered as a major potable, agricultural and industrial source of water in many locations. Groundwater was once thought to be preserved from contamination by of rock and soil layers, which act as filters. Depending on eighty-six wells, the aquifer formed by Dibdibba and alluvial fan in the eastern and northeastern part of the area while only Dibdibba formation forming the aquifer in the west of the area. The aquifer was investigated during fieldwork where geographical position, elevations, static water levels, depths, thicknesses, maximum yields as well as water sampling have been carried out. Depending on hydrochemical properties, the studied area characterize by groundwater polluted with salinity while a small area located to the west was unpolluted zone. Physicochemical analysis of groundwater aquifer is brackish to saline water. Groundwater quality of aquifer not recommended to be used for human and irrigation purposes, even so the farmers used this water for irrigation and animal purposes depending on soil nature and plants.